Susceptibility of ruminant livestock to experimental infection with SARS-CoV-2 and HPAIV H5N1 - Cool, Konner Robert (My University, 2025)
Emerging RNA viruses represent a constant and expanding threat to global public health, agriculture, and biosecurity. The recent panzootics of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and highly pathogenic avian influenza virus (HPAIV) H5N1 clade 2.3.4.4b illustrate how host-generalist viruses can infect a broad range of wildlife, companion, and food production animal species, sometimes sustaining transmission and spillover to humans. These events underscore the critical need to understand host susceptibility and potential transmission pathways early in an outbreak. The experiments described here were designed to investigate the susceptibility and transmission potential of ruminant hosts to SARS-CoV-2 and HPAIV H5N1 through controlled experimental infection studies. The objectives were to assess infection outcomes, viral shedding, within host virus competition, host adaptation, and potential animal-to-animal transmission following experimental exposure to each of these pathogens. The resulting data clarified the role of ruminant species in the respective pathogen ecology, reduced the uncertainty about undetected virus maintenance, and informed targeted surveillance and outbreak response. Collectively, these findings advanced our understanding of host range, intraspecies transmission, and the potential for these emerging zoonotic RNA viruses to establish new animal reservoirs.
Keywords: Experimental infection; Highly pathogenic avian influenza; Ruminant; Zoonotic; RNA virus; SARS-CoV-2